Effect of Different Core Slopes and Filters on Seepage for Horan Dam, Iraq - Qasim, Dhuha J.; Hussein, Haitham A.; Belew, Amanuel Zewdu (Al-Nahrain Journal for Engineering Sciences, 2025)
A dam failure results in losses in terms of economy and infrastructure, in addition to the loss of many lives and assets. Inadequate seepage control procedures are typically the cause of seepage failure in earth-fill dams. For an earthen dam to be waterproof and to minimize seepage, non-homogeneous dams with a clay core are one kind of embankment dam used. As water moves through the dam's core, friction causes it to lose a lot of energy. Both vertical and inclined cores can be used in the design and construction of zoned embankment dams. As a result, choosing the proper materials and dimensions for the earth dam's core is critical. The main objective of this study is to investigate different seepage control strategies for an earth dam (HORAN DAM) using the Finite Element Method (FEM). We modeled and analyzed nine cases of various seepage control techniques that have been modeled and analyzed using SEEP/W, a FEM-based software. The modeling results show using chimney filters reduces pore water pressure more effectively than using toe rock and horizontal filters. Regarding seepage, trapezoidal cores perform better than inclined cores, and the milder slope is preferred over steeper core slopes. The results show when the core permeability decreases, the seepage quantity also decreases. Toe rock decreases seepage more than horizontal filters and chimney filters. Additionally, it has been shown that using a toe rock filter together with a trapezoidal core with a mild slope performs better than using a different filter and a different internal clay core shape.